Role of Enteric Glia as Bridging Element between Gut Inflammation and Visceral Pain Consolidation during Acute Colitis in Rats - Elena Lucarini (MDPI AG, 2021)
Acute inflammation is particularly relevant in the pathogenesis of visceral hypersensitivity associated with inflammatory bowel diseases. Glia within the enteric nervous system, as well as within the central nervous system, contributes to neuroplasticity during inflammation, but whether enteric glia has the potential to modify visceral sensitivity following colitis is still unknown. This work aimed to investigate the occurrence of changes in the neuron–glial networks controlling visceral perception along the gut–brain axis during colitis, and to assess the effects of peripheral glial manipulation. Enteric glia activity was altered by the poison fluorocitrate (FC; 10 µmol kg−1 i.p.) before inducing colitis in animals (2,4-dinitrobenzenesulfonic acid, DNBS; 30 mg in 0.25 mL EtOH 50%), and visceral sensitivity, colon damage, and glia activation along the pain pathway were studied. FC injection significantly reduced the visceral hyperalgesia, the histological damage, and the immune activation caused by DNBS. Intestinal inflammation is associated with a parallel overexpression of TRPV1 and S100β along the gut–brain axis (colonic myenteric plexuses, dorsal root ganglion, and periaqueductal grey area). This effect was prevented by FC. Peripheral glia activity modulation emerges as a promising strategy for counteracting visceral pain induced by colitis.